Analysis of the Quality of Tax Services and Their Effect on Corporate Taxpayer Compliance in Reporting the Annual Corporate Income Tax Return (SPT E Filing) at KPP Pratama Banyuwangi - Didik Kuryana; Sumani Sumani; Mohammad Imam Farisi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The low level of taxpayer satisfaction with the quality of tax services causes the compliance of corporate taxpayers in reporting the annual corporate income tax return (SPT E Filing) at KPP Pratama Banyuwangi to decline. This study aims to determine the effect of tax service quality (Tangible, Reliability, Responsiveness, Assurance, and Empathy) on Corporate Taxpayer Compliance in Reporting Annual Income Tax Returns (SPT E Filing ) at KPP Pratama Banyuwangi. This research is quantitative research which includes correlation research. The population in this study were 1,472 corporate taxpayers in the form of a Commanditaire Venootschap or limited liability company (CV) that had submitted the 2020 Annual Corporate Income Tax Return by E Filing. Based on the table of F test results (simultaneous) it can be seen that the calculated F value (34.654) is greater than F table (F(0.05.5/308) = 2.243) and the Sig. in the table the value is 0.000 <0.05 so it can be concluded that the estimated linear regression model is feasible to use. This explains the significant effect of independent variables (Tangible, Reliability, Responsiveness, Assurance, and Empathy) simultaneously on the dependent variable (Taxpayer Compliance). The results of this study are in line with research conducted by Komala, et al (2014) which shows that the variables tangibles, reliability, responsiveness, assurance, empathy have a significant influence simultaneously and partially on taxpayer compliance.